Contribution To Empowerment Of Tourism Industry To Community Welfare - Azidni Rofiqo; Abdul Hamid; Tri Wijayanti Septiarini (EKOBIS SYARIAH, 2021)
This study aims to examine the effect of empowerment on welfare. Empowerment here is proxied by empowering, fostering, supporting, and protecting. Welfare is meant as a maqoshid sharia as measured by hifdz addin, an nafs, al nasl, al aql, and al mal. This study proposes a hypothesis of empowering, fostering, supporting, and protecting a positive effect on welfare. This research was conducted in 2019-2020 which took place at Ngebel Lake with 50 respondents in the tourism sector. This type of research is quantitative with questionnaire data collection that can be measured by a Likert scale. Data analysis through classical assumption test and multiple linear regression. The results of the analysis show that empowering, supporting, and protection have a significant positive effect on welfare. Fostering has no significant effect on welfare. Adjusted R-square value, 0.798119 which states that the four independent variables contributed 79% to the dependent variable. This research is limited to the place, time and samples. Future research is expected to be more comprehensive.